EFFECTIVENESS OF GALO-GALO HONEY SUPPLEMENTATION COMBINED WITH IRON TABLETS ON HEMOGLOBIN LEVELS AMONG FEMALE MIDWIFERY STUDENTS - Ira Suryanis; Rinita Amelia; Dessy Abdullah; Fauziah Fadhilatul Rizka Yudha; Yudha Endra Pratama (Nusantara Hasana Journal, 2026)
Background: Anemia remains an important nutritional problem among adolescent girls and young women. Female university students are vulnerable to iron deficiency because of menstrual blood loss, inadequate dietary iron intake, and irregular eating patterns. This study evaluated the effectiveness of Galo-Galo honey supplementation combined with iron tablets in increasing hemoglobin levels among female midwifery students. Methods: A quantitative pre-experimental study with two pretest-posttest groups was conducted among 38 female students of the Bachelor of Midwifery Program, Faculty of Health Sciences, Universitas Baiturrahmah, Padang. Participants were allocated into two groups of 19 students. One group received iron tablets combined with Galo-Galo honey, while the comparison group received iron tablets. Hemoglobin was measured before and after the intervention using an EasyTouch GCHb device. Results: In the iron tablet plus Galo-Galo honey group, mean hemoglobin increased from 12.4 ± 1.2534 g/dL before intervention to 13.2 ± 1.2810 g/dL after intervention, representing a mean increase of 0.8 g/dL (p<0.001). In the iron-tablet group, mean hemoglobin increased from 11.9 ± 0.957 g/dL to 12.6 ± 0.875 g/dL, representing a mean increase of 0.7 g/dL (p<0.001). Conclusion: Both interventions were associated with significant increases in hemoglobin levels. The observed increase was numerically greater in the combination group; however, the source document does not report a statistical test directly comparing the magnitude of hemoglobin change between groups. Further controlled studies with larger samples are required to establish the additional effect of Galo-Galo honey beyond iron supplementation.